2021
DOI: 10.3389/fonc.2021.687374
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Decitabine and a Modified Regimen of Cisplatin, Cytarabine and Dexamethasone: A Potential Salvage Regimen for Relapsed or Refractory Diffuse Large B-Cell Lymphoma After Second-Line Treatment Failure

Abstract: ObjectiveThe prognosis for patients with relapsed or refractory diffuse large B-cell lymphoma (R/R-DLBCL) after second-line treatment failure is extremely poor. This study prospectively observed the efficacy and safety of decitabine with a modified cisplatin, cytarabine, and dexamethasone (DHAP) regimen in R/R-DLBCL patients who failed second-line treatment.MethodsTwenty-one R/R-DLBCL patients were enrolled and treated with decitabine and a modified DHAP regimen. The primary endpoints were overall response rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…For the cell line with the most pronounced response to Dexamethasone treatment, OCI-LY1, the in vitro findings could also be recapitulated in the corresponding in vivo xenograft model. This confirms that at least the corticosteroid component of stabilizing chemotherapy regimens in DLBCL patients [ 8 , 9 ] prior to CXCR4-targeted RLT with [ 177 Lu]Lu-PentixaTher does not lead to downregulation of the molecular target CXCR4 and may even have a contrary, beneficiary effect. However, it needs to be investigated in more detail to which extent rituximab or the other chemotherapeutic agents used in CHOP or DHAP treatment protocols affect CXCR4 expression, since these effects may limit the use of CXCR4-targeted diagnostics and/or CXCR4-targeted therapies [ 4 ].…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…For the cell line with the most pronounced response to Dexamethasone treatment, OCI-LY1, the in vitro findings could also be recapitulated in the corresponding in vivo xenograft model. This confirms that at least the corticosteroid component of stabilizing chemotherapy regimens in DLBCL patients [ 8 , 9 ] prior to CXCR4-targeted RLT with [ 177 Lu]Lu-PentixaTher does not lead to downregulation of the molecular target CXCR4 and may even have a contrary, beneficiary effect. However, it needs to be investigated in more detail to which extent rituximab or the other chemotherapeutic agents used in CHOP or DHAP treatment protocols affect CXCR4 expression, since these effects may limit the use of CXCR4-targeted diagnostics and/or CXCR4-targeted therapies [ 4 ].…”
Section: Resultssupporting
confidence: 63%
“…Clinically, in the management of DLBCL, the combination of CHOP (Cyclophosphamide, Doxorubicin, Vincristine and Prednisone a ) and rituximab is considered a standard first-line treatment [ 8 ], whereas modified/extended DHAP (Dexamethasone, Cytarabine, Cisplatin) protocols are used as second-line chemotherapies [ 9 ]. Since patients with DLBCL eligible for [ 177 Lu]Lu/[ 90 Y]Y-PentixaTher RLT are very likely to undergo/have undergone one of these treatments, Prednisolone 1 and Dexamethasone were both included into this investigation.…”
Section: Background and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It displays cytotoxicity at high concentrations, whereas low doses can minimize toxicity and may improve the targeting effect of DNA hypomethylation through a re-expression of tumor suppressor genes during tumor therapy (133). A phase 4 clinical trial investigated the efficacy of a combination of decitabine together with a modified regimen of cisplatin, cytarabine, and dexamethasone (DHAP) in relapsed/refractory DLBCL (r/r DLBCL) (134). The results showed that overall response rate (ORR) reached 50% and complete response rate (CRR) reached 35%.…”
Section: Dnmt Inhibitors 2211 Decitabinementioning
confidence: 99%
“…follicular lymphoma and small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL), or aggressive subtypes, such as diffuse large B-cell lymphoma (DLCBL) and Burkitt lymphoma (BL) [12,13]. The standard rst-line therapy for aggressive lymphomas, based upon polychemotherapy plus the anti-CD20 antibody rituximab, yields about 60% of responders [14,15]; however, for patients who do not respond to rst-line therapies and failed second options, representing about the 30-40% of cases, treatment outcomes are very poor [16,17].…”
mentioning
confidence: 99%